The Slovenian Language, Literature and Teaching of Slovenian Language Research Project - Jesenšek, Marko (Slavia Centralis, 2020)
The Slovenian language, literature and teaching of Slovenian language research project explores the role of Slovenian both in its native Slovenia and in contact with the neighbouring languages. It combines diachronic and synchronic approaches to the study of Slovenian in contact with other languages in the Danube and the Alps-Adriatic regions. In addition, it examines its contact with Global English.
Keywords: history of the Slovenian language; language policy and planning; dialectology; Slovenian grammar and lexicology; Slovenian literature; multiculturality and interculturality; didactics of language and literature